Carbonate system variability in the Mediterranean Sea: a modelling study - Tsiaras, Kostas; Frangoulis, Constantin; Stamataki, Natalia (Frontiers in Marine Science, 2024)
A basin-scale Mediterranean carbonate system model has been setup, building on the POSEIDON operational biogeochemical model. The spatial variability of carbonate system variables from a 13-year simulation (2010-2022) was validated against CARIMED in situ data (DIC, TA, pCO2), showing reasonable agreement in reproducing the observed patterns and preserving the dynamics in different areas, except a slight overestimation ( 15 µmol/kg) of TA in the Eastern Levantine. The time-variability of model outputs (DIC, TA, pCO2, pH) was validated, against available time-series from Western (DYFAMED, Villefranche-PointB) and Eastern Mediterranean (HCB) sites, showing good agreement with the data, particularly for pCO2, pH and DIC. The model failed to reproduce the observed late summer peak of TA at DYFAMED/PointB sites, which may be partly attributed to the advection of lower alkalinity Atlantic water in the area. The seasonal variability of DIC and pCO2@20°C was found to be mainly controlled by winter mixing and the subsequent increase of primary production and net CO2 biological uptake, which appeared overestimated at HCB. Along with the reference simulation, three sensitivity simulations were performed, de-activating the effect of biology, evaporation and CO2 air-sea fluxes on DIC and TA, in order to gain insight on the processes regulating the simulated carbonate system variability. The effect of biological processes on DIC was found more significant (peak during spring) in the more productive North Western Mediterranean, while evaporation had a stronger impact (peak during late summer) in the Levantine basin. CO2 air-sea flux was higher in the Western Mediterranean, particularly the Gulf of Lions and Alboran Sea, as well as in river influenced areas, such as the N. Adriatic and along the pathway of the Black Sea Water in the Aegean. A weak release of CO2 was found in the Eastern Levantine and Libyan Sea. Its basin average (+2.1 mmol/m2/day) and positive trend (+0.1 mmol/m2/day/year) indicates a gradually increasing net CO2 ocean uptake. The simulated positive trends of DIC (0.77 μmol/kg/year) and TA (0.53 μmol/kg/year) in the North Western Mediterranean were consistent with observational and modelling studies, in constrast with the Levantine basin, where no significant trends were found for TA.